Depletion of m6A-RNA in Escherichia coli reduces the infectious potential of T5 bacteriophage - Bibakhya Saikia; Sebastian Riquelme-Barrios; Thomas Carell; Sophie Brameyer; Kirsten Jung (Microbiology Spectrum)
ABSTRACT N6-Methyladenosine (m6A) is the most abundant internal modification of mRNA in eukaryotes that plays, among other mechanisms, an essential role in virus replication. However, the understanding of m6A-RNA modification in prokaryotes, especially in relation to phage replication, is limited. To address this knowledge gap, we investigated the effects of m6A-RNA modifications on phage replication in two model organisms: Vibrio campbellii BAA-1116 (previously Vibrio harveyi BB120) and Escherichia coli MG1655. An m6A-RNA-depleted V. campbellii mutant (ΔrlmFΔrlmJ) did not differ from the wild type in the induction of lysogenic phages or in susceptibility to the lytic Virtus phage. In contrast, the infection potential of the T5 phage, but not that of other T phages or the lambda phage, was reduced in an m6A-RNA-depleted E. coli mutant (ΔrlmFΔrlmJ) compared to the wild type. This was shown by a lower plaquing efficiency and a higher percentage of surviving cells. There were no differences in the T5 phage adsorption rate, but the mutant exhibited a 5-min delay in the rise period during the one-step growth curve. This is the first report demonstrating that E. coli cells with lower m6A-RNA levels have a higher chance of surviving T5 phage infection.IMPORTANCEThe importance of RNA modifications has been thoroughly studied in the context of eukaryotic viral infections. However, their role in bacterial hosts during phage infections is largely unexplored. Our research delves into this gap by investigating the effect of host N6-methyladenosine (m6A)-RNA modifications during phage infection. We found that an Escherichia coli mutant depleted of m6A-RNA is less susceptible to T5 infection than the wild type. This finding emphasizes the need to further investigate how RNA modifications affect the fine-tuned regulation of individual bacterial survival in the presence of phages to ensure population survival.